Ablation of epicardial premature ventricular contractions in a patient with ischemic cardiomyopathy and implementation of cardiac resynchronization therapy in the same procedure - Veysel Kutay Vurgun; Başar Candemir; Ali Timuçin Altın; Ömer Akyürek (KARE Publishing, 2017)
Premature ventricular contractions (PVCs) can cause clinical deterioration in patients with heart failure and increase the frequency of shocks delivered by an implantable cardioverter defibrillator (ICD). Epicardial PVC/ventricular tachycardia (VT) is seen less often in ischemic cardiomyopathy. Radiofrequency catheter ablation is the most effective treatment option for the management of PVC/VT and can improve cardiac function. Presently described is a patient with ischemic cardiomyopathy and frequent PVCs and VT runs with multiple ICD therapies who was treated with simultaneous radiofrequency catheter ablation in the anterior interventricular vein and cardiac resynchronization therapy defibrillator upgrade in the same procedure.